Comparative metabolomics of flavonoids in twenty vegetables reveal their nutritional diversity and potential health benefits. (February 2023) - Tao, Han; Zhao, Yao; Li, Linying; He, Yuqing; Zhang, Xueying; Zhu, Ying; Hong, Gaojie
Graphical abstract: Highlights: There are 403 flavonoids detected in 20 vegetables that we consume daily. Flavonoids are relatively abundant in bean sprouts, while lower in Zizania latifolia . Apigenin and diosmin are most abundant in bean sprouts. Bean sprouts are found to possess significant antioxidant enzyme activity. Abstract: Vegetables are rich in flavonoids and are widely consumed in our daily life. However, comprehensive information on flavonoids components in vegetable varieties and the distribution of flavonoids with health-promoting effects in different vegetables are rarely investigated. Here, we analyzed the constitution of flavonoids among 20 vegetables by widely-targeted metabolome analysis. A total of 403 flavonoids were detected and classified as flavonoid, flavonols, anthocyanins, isoflavones, flavonoid carbonoside, dihydroflavone, chalcones, flavanols, dihydroflavonol, tannin, proanthocyanidins, and other flavonoids. Interestingly, we found that the content and types of flavonoids in bean sprouts and hot pepper were relatively abundant, whereas those were lower in carrot, lettuce, and Zizania latifolia . Then, we characterized the representative flavonoids including flavonoid, flavonols, chalcones, and isoflavones, and related them to the health-promoting effects of vegetables. Finally, we examined the relevance of the flavonoids to antioxidant capacity. Both bean sprouts and hot pepper possessed higher antioxidant enzyme activity, which were responsible for their great antioxidant capacity. Our study established a database of major flavonoids components in vegetables and further provides a new hint for the selection and breeding of vegetables based on their health-promoting effects.